Mineral trioxide aggregate improves healing response of periodontal tissue to injury in mice - Vidovic Zdrilic, I.; Azevedo Queiroz, I. O. de; Matthews, B. G.; Gomes-Filho, J. E. [UNESP]; Mina, M.; Kalajzic, I. (Wiley-Blackwell, 2017)
Background and Objective: Mineral trioxide aggregate (MTA) is a biomaterial used in endodontic procedures as it exerts beneficial effects on regenerative processes. In this study, we evaluate the effect of MTA on healing of periodontal ligament (PDL) and surrounding tissue, following injury, in a transgenic mouse model and on the differentiation of murine mesenchymal progenitor cells in vitro. Material and Methods: We used an inducible Cre-loxP in vivo fate mapping approach to examine the effects of MTA on the contributions of descendants of cells expressing the SMA-CreERT2 transgene (SMA9(+)) to the PDL and alveolar bone after experimental injury to the root furcation on the maxillary first molars. Col2.3GFP was used as a marker to identify mature osteoblasts, cementoblasts and PDL fibroblasts. The effects of MTA were examined 2, 17 and 30days after injury and compared histologically with sealing using an adhesive system. The effects of two dilutions of medium conditioned with MTA on proliferation and differentiation of mesenchymal progenitor cells derived from bone marrow (BMSC) and periodontal ligament (PDLC) in vitro were examined using the PrestoBlue viability assay, alkaline phosphatase and Von Kossa staining. The expression of markers of differentiation was assessed using real-time PCR. Results: Histological analyses showed better repair in teeth restored with MTA, as shown by greater expansion of SMA9(+) progenitor cells and Col2.3GFP(+) osteoblasts compared with control teeth. We also observed a positive effect on differentiation of SMA9(+) progenitors into osteoblasts and cementoblasts in the apical region distant from the site of injury. The in vitro data showed that MTA-conditioned medium reduced cell viability and osteogenic differentiation in both PDLC and BMSC, indicated by reduced von Kossa staining and lower expression of osteocalcin and bone sialoprotein. In addition, cultures grown in the presence of MTA had marked decreases in SMA9(+) and Col2.3GFP(+) areas as compared with osteogenic medium, confirming reduced osteogenesis. Conclusion: MTA promotes regeneration of injured PDL and alveolar bone, reflected as contribution of progenitors (SMA9(+) cells) into osteoblasts (Col2.3GFP(+) cells). In vitro, MTA-conditioned medium fails to promote osteogenic differentiation of both PDLC and BMSC.
Keywords: differentiation; injury; MTA; periodontal ligament; progenitor cells